2021
DOI: 10.21203/rs.3.rs-892486/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

NDRG2 Inhibits Pyruvate Carboxylase-Mediated Anaplerosis and Combines with Glutamine Blockade To Inhibit The Growth of Glioma

Abstract: Background Due to the rapid proliferation, cancer cells have increased anabolic biosynthesis, which requires anaplerosis to replenish precursor intermediates. The major anaplerotic sources are pyruvate and glutamine, which require the catalysis of pyruvate carboxylase (PC) and glutaminase (GLS) respectively. In GLS-suppressed cancer cells, the PC-mediated pathway for anaplerosis is crucial to maintain cell growth and proliferation. Here, we investigated the regulatory role and molecular mechanism of the tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…GBM relies on PC for the glucose-dependent replenishment of the TCA cycle with intermediates, a process known as anaplerosis [ 47 ]. The tumor suppressor NDRG2 inhibits PC expression in IDH-mutant and suppresses glioma growth but this was not observed for IDH-wildtype [ 48 ]. Furthermore, NDRG2 induces the ubiquitination and degradation of PC under glutamine deficiency, and NDRG2 loss leads to increased PC and PC-dependent anaplerosis and glioma tumorigenesis [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GBM relies on PC for the glucose-dependent replenishment of the TCA cycle with intermediates, a process known as anaplerosis [ 47 ]. The tumor suppressor NDRG2 inhibits PC expression in IDH-mutant and suppresses glioma growth but this was not observed for IDH-wildtype [ 48 ]. Furthermore, NDRG2 induces the ubiquitination and degradation of PC under glutamine deficiency, and NDRG2 loss leads to increased PC and PC-dependent anaplerosis and glioma tumorigenesis [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The tumor suppressor NDRG2 inhibits PC expression in IDH-mutant and suppresses glioma growth but this was not observed for IDH-wildtype [ 48 ]. Furthermore, NDRG2 induces the ubiquitination and degradation of PC under glutamine deficiency, and NDRG2 loss leads to increased PC and PC-dependent anaplerosis and glioma tumorigenesis [ 48 ]. In vivo studies have demonstrated that aerobic glycolysis is insufficient to contribute to cellular anaplerosis and support GBM tumor cell growth [ 19 ].…”
Section: Discussionmentioning
confidence: 99%